Solitary Rectal Ulcer Syndrome in Patients Presenting with Lower Gastrointestinal Bleeding - Nowsherwan, Rashid Ahmad, Nawaz Khan, Ghazala Shaheen, Umair Latif, Zia Ul Haq, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Solitary Rectal Ulcer Syndrome (SRUS) remains a rare, often overlooked identification of lower gastrointestinal bleeding due to its overlap with other colorectal disorders. It is usually preceded by chronic constipation and, in some circumstances, rectal prolapse. This study investigates the clinical data, treatment results, pathology, endoscopic, and histological features of diagnosed SRUS lesions in patients with lower gastrointestinal bleeding. Methods: This prospective observational research was done at the Peshawar Institute of Medical Sciences, Hayatabad, from January 2022 to December 2022. A total of 101 adults suffering from rectal bleeding were included in the study. Clinical symptoms were noted using a precise capturing tool. Every participant underwent either sigmoidoscopy or colonoscopy and received biopsy specimens for histological validation. A tailored approach to treatment was taken, and results were evaluated following an observation period of at least three months. Results: Most patients were between 30 and 50 years of age, with a slight male predominance. Constipation (76.2%), straining (80.2%), and mucus discharge (61.4%) were among the most common symptoms. Most ulcers were solitary and located on the anterior or posterior rectal wall. Histopathological findings included fibromuscular obliteration and glandular crypt distortion in most cases. Conservative and medical treatment improved symptoms in 75.2% of patients, while 17.8% required surgical intervention. Recurrence was noted in 21.8% of cases. Conclusion: SRUS should be taken into account in patients suffering from chronic rectal bleeding and defecation difficulties. An endoscopic procedure and a biopsy remain critical for obtaining a diagnosis. Early identification paired with tailored therapies allies with positive outcomes; however, the potential recurrence in some patients is troubling. Keywords: Solitary Rectal Ulcer Syndrome, Rectal Bleeding, Constipation, Endoscopy, Histopathology, Treatment Outcome, Rectal Prolapse, Peshawar Institute of Medical Sciences.